Optimasi Paket Pupuk Tunggal pada Tanaman Kelapa Sawit Belum Menghasilkan Umur Satu Tahun - Saputra, Hidayat; ,, Sudradjat; Yahya, sudirman (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2015)
ABSTRACTEffective and efficient fertilization is affected by fertilizer dose, and therefore information on the appropriate dose of a single fertilizer for oil palm will be beneficial to increase the efficiency and effectiveness of fertilization in oil palm plantations. The objectives of this research were to study the response patterns and to determine optimum rate of single fertilizer package related to the growth of one year old oil palm trees. The experiment was conducted from March 2013 to February 2014 at IPB-Cargill Teaching and Research Farm of Oil Palm, Jonggol Bogor. The experiment was arranged in randomized block design with one factor and replicated three times. The treatments were four single fertilizer package as followed: control, 300 g urea + 375 g SP-36 + 350 g KCl + 25 g boric acid + 25 g CuSO4.5H2O, 600 g urea + 750 g SP-36 + 700 g KCl + 25 g boric acid + 25 g CuSO4.5H2O, 900 g urea + 1125 g SP-36 + 1050 g KCl + 25 g boric acid + 25 g CuSO4.5H2O per plant. The result showed that application of single fertilizer package significantly increased the growth of young oil palm linearly as shown by plant height, stem girth, leaf area of frond number 9, chlorophyll and P content of the leaves and quadratically on leaf number at the last observation. The optimum rate of single fertilizer for one year old oil palm trees had not been attained at this research because the plant growth response to fertilization was still linear.Keywords: inorganic, leaf frond number 9, optimum rate, growth response, stem girth